2007
DOI: 10.3319/tao.2007.18.1.55(t)
|View full text |Cite
|
Sign up to set email alerts
|

Low-Angle Reverse Faulting During Two Earthquakes on the Northern Part of the Chelungpu Fault, Deduced From the Fengyuan Trench, Central Taiwan

Abstract: ABSTRACT1 Yokohama National University, Yokohama, Japan Terr. Atmos. Ocean. Sci., Vol. 18, No. 1, March 2007 56 for horizontal and ca. 5 m for vertical) than those (2.7 m for horizontal and ca. 2 m for vertical) of the 1999 earthquake. The age of the penultimate earthquake at the Fengyuan site is the oldest earthquake recorded among the known penultimate penultimate events on the Chelungpu fault so far and suggests that this part of the Chelungpu fault may be a fault segment independent of the central and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The single trench site located on the northern Chelungpu fault revealed only one paleo-earthquake that occurred 1.4-2.0 ka BP [Ota et al, 2007], a time period when surface ruptures are also documented on the southern and central parts of the fault, suggesting that a single earthquake could have ruptured the entire Chelungpu fault system, as Chi-Chi did. As mentioned by Ota et al [2007], it is likely that other paleo-earthquakes ruptured another identified, but unexcavated, active branch of the fault near the northern site. Although more intricate scenarios of earthquakes sequence are possible based on current paleoseismological data, these data do not contradict the idea that Chi-Chi could be a characteristic earthquake for the Chelungpu-Sanyi fault system.…”
Section: Along-strike Kinematics Of the Chelungpu-sanyi Fault System:mentioning
confidence: 93%
See 2 more Smart Citations
“…The single trench site located on the northern Chelungpu fault revealed only one paleo-earthquake that occurred 1.4-2.0 ka BP [Ota et al, 2007], a time period when surface ruptures are also documented on the southern and central parts of the fault, suggesting that a single earthquake could have ruptured the entire Chelungpu fault system, as Chi-Chi did. As mentioned by Ota et al [2007], it is likely that other paleo-earthquakes ruptured another identified, but unexcavated, active branch of the fault near the northern site. Although more intricate scenarios of earthquakes sequence are possible based on current paleoseismological data, these data do not contradict the idea that Chi-Chi could be a characteristic earthquake for the Chelungpu-Sanyi fault system.…”
Section: Along-strike Kinematics Of the Chelungpu-sanyi Fault System:mentioning
confidence: 93%
“…The southern part of the fault might rupture in a different fashion, in paired earthquakes every ~700–800 years, possibly suggesting contribution from a different type of event possibly rupturing from the south. The single trench site located on the northern Chelungpu fault revealed only one paleo‐earthquake that occurred 1.4–2.0 ka BP [ Ota et al ., ], a time period when surface ruptures are also documented on the southern and central parts of the fault, suggesting that a single earthquake could have ruptured the entire Chelungpu fault system, as Chi‐Chi did. As mentioned by Ota et al .…”
Section: Kinematics Of the Northern Chelungpu Fault And Distribution mentioning
confidence: 99%
See 1 more Smart Citation